Synthesis of amorphous hollow Ni(HCO3)2 nanostructures with excellent supercapacitor performance from nickel-containing electroplating sludge. Issue 1 (February 2022) - Hou, Zhiyan; Meng, He; Shao, Xueqing; Wang, Xianglong; Tahir, M. Usman; Ahmad, Shakiaz; Yang, Chao; Su, Xintai; Zhang, Lijuan
Abstract: The complex composition and recycling process of electroplating sludge are the two major obstacles restricting the recycling of metal resources. In this work, Ni(HCO3 )2 hollow spheres with unique amorphous structure were prepared via a simple and controllable hydrothermal method using nickel-containing electroplating sludge as raw material and ascorbic acid (AA) as complexing agent. The introduction of AA not only changed the morphology of the sample, but also formed pure phase Ni(HCO3 )2 . The controllable amorphous structure is beneficial to the diffusion of OH - in the electrolyte. More importantly, its disordered atomic arrangement and metastable structure provide a large number of active sites and ion transmission channels, which improve the specific capacity. Consequently, amorphous Ni(HCO3 )2 delivers a large capacitance of 599.8 C g −1 at 1 A g −1, besides large capacitance, it also exhibits large rate capability (61.02% at a current density of 10 A g −1 ) and cycle performance (capacitance retention 52.09% after 1000 cycles). Importantly, the recoveries of nickel, iron and aluminum are 95.57%, 99.92% and 92.30%, respectively, indicating that electroplating sludge has a good application prospect as electrode materials for supercapacitors. Graphical Abstract: ga1 Highlights: The electroplating sludge is converted into amorphous nickel bicarbonate self-assembled hollow spheres. The temperature has a decisive influence on the crystalline state of the sample. The ascorbic acid changes the surface characteristics of the nanoparticles to form a hollow structure. The recoveries of Ni, Fe and Al are 95.57%, 99.92% and 92.30%, respectively.